Efektivitas Peraturan Daerah Kota Pangkalpinang Nomor 7 Tahun 2019 tentang Penyelenggaraan Ketertiban Umum dan Ketentraman Masyarakat (Studi Kasus Terhadap Penertiban Pedagang Kaki Lima) - Putri Santoso, Yulika; Toni, Toni; Agustian, Rio Armanda (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
Street vendors are individuals engaged in trading activities using movable or immovable means, utilizing city infrastructure, social facilities, public facilities, and land or buildings owned by the government or private entities that are temporary or non-permanent. The activities of street vendors disrupt public order and cause traffic congestion. This study aims to analyze the effectiveness of the Pangkalpinang City Regional Regulation No. 7 of 2019 concerning the Organization of Public Order and Community Tranquility, specifically related to the regulation of street vendors. The background of this research focuses on the increasing number of street vendors operating in public spaces, such as sidewalks and roadways, which disrupts the order and comfort of the community. The research method used is a juridical-empirical approach with legal and case studies, involving interviews and field observations. The results indicate that although the regulation has been established, its implementation still faces various challenges, such as a lack of public knowledge about the regulations, limited trading locations, and a culture of tolerance towards the presence of street vendors. Law enforcement by the Civil Service Police Unit (Satpol PP) is also deemed ineffective, given the numerous violations occurring. This study recommends the need for better socialization regarding the regulations, as well as the establishment of designated zones for street vendors to operate without disrupting public order. Thus, it is hoped that this regulation can be more effective in creating order and tranquility in the community of Pangkalpinang City.